Effect of sintering aid (CoO) on transport properties of nanocrystalline Gd doped ceria (GDC) materials prepared by co-precipitation method - Baral, Ashok Kumar; Dasari, Hari Prasad; Kim, Byung-Kook; Lee, Jong-Ho (ELSEVIER SCIENCE SA, 2013)
Electrical and dielectric properties of the nanocrystalline GDC materials co-doped with CoO (by deposition precipitation method) were studied in the temperature range of 150-600 degrees C. CoO co-doped samples show higher grain interior conductivity than that of GDC. Dielectric loss tangent (tan delta) shows the presence of defect associates such as (Co - V-<(o)double over dot> - Co) and (Co - V-<(o)double over dot>) in co-doped samples in addition to the defects (Gd - V-<(o)double over dot> - Gd) and (Gd - V-<(o)double over dot>) that are present in GDC system. Dynamic parameters such as migration energy and association energy of oxygen vacancies do not vary significantly with co-doping CoO in the GDC materials. With higher content of CoO, excess of Co2+ in the grain boundary regions leads to trapping of vacancies and/or depletion of vacancies in the space charge region. Therefore grain boundary activation energy increases and grain boundary conductivity decreases with CoO content above 1 mol%, at lower temperatures. In the temperature range of 150-600 degrees C overall conductivities in CoO co-doped samples increase two to three times than that of GDC material. (C) 2013 Elsevier B. V. All rights reserved.
Keywords: ELECTRICAL-CONDUCTIVITY; SINTERABILITY; RELAXATION; SM